The identity of Tai-Yai ethnic to promote community tourism in Mae Hong Son Province, Thailand - Sasong, Sanya (Linguistics and Culture Review, 2021)
This study of the identity of Tai-Yai ethnic to promote community tourism in Mae Hong Son province is a participatory action research that aimed to find a format for building a learning center for Tai-Yai identity and to establish a network of Tai-Yai identity conservation groups that is linked to community tourism in Mae Hong Son Province. This study focused on the way of life and identity of Tai-Yai people in five districts in Mae Hong Son province include Pai, Pang Mapha, Muang, Khun Yuam, and Mae La Noi. The results of the research were as follows: the Tai-Yai communities maintain their way of life, the concept of belief in the supernatural, and Buddhism beliefs, pass on their identity to the younger generation, and transfer their identity to the general public. The Tai-Yai community of Pambok village has the potential to build a learning center for the Tai-Yai identity at the community level by linking with the Tai-Yai Education Center, Mae Hong Son province which is a “FICES” model (Sustainable Education Community Identity of Tai-Yai Faith).